How do the social changes influence the English language grammar? - Ljubičić Gordana M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2021)
The paper deals with recent changes occurring in the English language due to the changes in the society itself. Every language is influenced by the changes happening in every aspect of human life, namely, in politics, economics, culture or human relations. The topic of the paper is how the changes in gender relations influence the English grammar, that is, the part of the grammar dealing with English pronouns. Nowadays, many people, transgender or others, refuse to be denoted by singular pronouns "he" or "she" - and choose the singular "they" instead. Although this use of "they" is not such a new thing, because the nonbinary pronoun "they" was voted the Word of the Year 2015 by American Dialect Society and again in 2019 as the Word of the Decade by the same institution, people are still sceptic about its grammatical correctness. But, this use of the pronoun is gaining in popularity, and very soon, the English language might accept these changes.